Reception of Pragmatism in Postphilosophy - Baranova, Jūratė (Problemos, 2002)
What unites philosophers from two different philosophical cultures: William James, who wrote at the end of XIX and at the beginning of XX century and contemporary postmodemists - Richard Rorty and Jacques Derrida? Why Rorty considers the jamesean turn in philosophy as parallel to Friedrich Nietsche's impact to the break of philosophical thought? How and why the idea of deconstruction corresponds to the paradigm of postmodern thinking? What are the common points of view between the “mystery”, which is presupposed at derridean ethics of deconstruction and the “jump across the abyss” which is the main leitmotif in William James's doctrine on the will to believe? Why pragmatist nevertheless is not deconstructionist? This article analyses and criticizes the attemps of Richard Rorty to bring together closer William James and Jacques Derrida. On the other hand, it does see some possible common parallels between these two strands of thought.